Automotive Prosthetic : Technological Mediation and the Car in Conceptual Art - Terranova, Charissa N. (University of Texas Press, 2014)
An in-depth examination of the use of the car, the driver, and the road in a variety of forms of creative expression, ranging from works by Robert Rauschenberg and Martha Rosler to those of Dan Graham, John Cage, and Dennis Hopper.